VUCA environments before the recession caused by covid-19: a systematic literature review - Woltés, Vicente (2023)
The acronym VUCA as a description of a Volatile, Uncertain, Complex and Ambiguous environment, has been gaining increasing relevance as a noun to describe a reality that is complex and turbulent. Besides the healthcare challenges, the COVID-19 pandemic has also caused drastic changes in the management world. Through a systematic literature review of 137 articles published before the beginning of the COVID-19 pandemic (between 2009 and March 2020), we develop a conceptual framework that integrates complementary branches of theoretical and empirical research, with the VUCA environment as the central unit of analysis. Our objectives are to unravel how the main theories in this field address essential aspects of management and future study trends, we also propose a conceptualisation of VUCA as an essential element of the current environment and its relationship with the different disciplines in the business world.